Solidarność . biuletyn informacyjny, no. 31, 1981 - Komitet Założycielski Niezależnych Samorządnych Związków Zawodowych, [ed. Stefan Adamski et al.] (KZ NSZZ "Solidarność", 1981)
Creation and circulation: Issues no. 15(1980)-no 32=62(1981) and from issue no. 19[i.e.17]=232(1989) published legally. Afther the introduction of the Martial Law published underground, with numeration continous with the 1980-1981 publication